2002
DOI: 10.1177/000348940211101010
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Tuberculosis: A Report of 15 Cases

Abstract: Laryngeal tuberculosis is usually a complication of pulmonary tuberculosis. Recent studies have described a change in the clinical features of laryngeal tuberculosis. We present 15 cases of laryngeal tuberculosis treated at the Osaka Prefectural Habikino Hospital between 1993 and 2000. The results showed a mean age of 51 years, a male predominance by 2.75 to 1, and a 20% incidence (n = 3) of negative chest radiographic findings. The prominent presenting symptom was hoarseness (73.3%), and systemic symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
8
27
1
2
Order By: Relevance
“…8,10 Various studies in the past had stated that mycobacterium tuberculosis usually involves the posterior part of the larynx with lesions usually found to involve the interarytenoid region, the arytenoids and the posterior glottis and was believed to be due to pooling of infected sputum in the recumbent position. 5,8,10 In our study however we found the vocal cords (diffuse) to be the most common site of involvement which was similar to the findings of Shin et al and Clery et al 8,12 Based on macroscopic appearance, Shin et al classified their fibreoptic findings into ulcerofungative mass lesion, whitish ulcerative lesion, nonspecific inflammatory lesion and polypoid lesion and found that ulcerative lesions were the commonest (40.9%) in their study. In our study we observed that both in single and multiple lesions in the larynx, ulcerative lesions was the most common finding.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…8,10 Various studies in the past had stated that mycobacterium tuberculosis usually involves the posterior part of the larynx with lesions usually found to involve the interarytenoid region, the arytenoids and the posterior glottis and was believed to be due to pooling of infected sputum in the recumbent position. 5,8,10 In our study however we found the vocal cords (diffuse) to be the most common site of involvement which was similar to the findings of Shin et al and Clery et al 8,12 Based on macroscopic appearance, Shin et al classified their fibreoptic findings into ulcerofungative mass lesion, whitish ulcerative lesion, nonspecific inflammatory lesion and polypoid lesion and found that ulcerative lesions were the commonest (40.9%) in their study. In our study we observed that both in single and multiple lesions in the larynx, ulcerative lesions was the most common finding.…”
Section: Discussionsupporting
confidence: 90%
“…These finding are similar to other studies which documented ages ranging in the fourth and fifth decade of life. 5,8 Hoarseness of voice was found to be the most common symptom which was found in fourteen (93%) cases. This finding is similar to that of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larengeal tüberküloz, 5. ve 6. dekadlarda ve erkeklerde (E/K=2/1) daha sık görülmektedir [8]. Hemen her zaman aktif akciğer tüberkülozu ile birliktedir [3].…”
Section: Discussionunclassified
“…Earlier, it affected posterior larynx in most patients, since it directly spreads along the airway [1][2][3][4][5][6]. Currently, however, it is prevalent in all parts of the larynx and is usually seen in people in their 40s-60s as primary laryngeal tuberculosis.…”
Section: Introductionmentioning
confidence: 99%